O papel da assessoria pedagógica no desenvolvimento profissional de professores da educação superior: a realidade de uma faculdade privada da Bahia - Santos, Nandyara Souza (2015)
This dissertation is the result of an empirical research, with a qualitative approach, conducted as one of the requirements of the Master in Education Degree of the Universidade Estadual de Feira de Santana. It discusses the role of pedagogical counseling in pedagogical training of higher education professors, seeing it as referent to professional development. The research was based on the emerging paradigm of science (SOUSA SANTOS, 1995), characterized by complexity and transdisciplinarity (MORAES and VALENTE, 2008) in dialogue with the Theory of Social Representations (Moscovici, 2003; 2013) (JODELET, 2001). It also dialogued with the reflections of the higher education teaching field (Cunha, 1998; Ristoff, 2006), the pedagogical training of the university teaching professionals (Vasconcelos, 2000; PIMENTA and ANASTASIOU, 2002; TARDIF, 2007; SOARES and CUNHA, 2010), and pedagogical counseling (LUCARELLI, 2002 and 2008; CUNHA, 2012 and 2014) and arouse from the following research question: according to the representations of teachers of a private university of Bahia, which are the contributions from the pedagogical counseling sector for the professional development of these subjects? Empirical research was performed at a private college of Bahia, and seven undergraduate courses professors of the allusive institution of higher education participated. In order to constitute the corpus of research, we conducted semistructured interviews, with exmanent type questions (JOVCHELOVITCH and BAUER, 2002). Parts of meaning were organized, analyzed and discussed from the theoretical and methodological principles of Content Analysis (BARDIN, 2011). As achieved results, we observed that the professors consider teaching in higher education as a complex activity, with their professional identity oscillating between vocation and professionalism, and some teachers believe that dominion of methods and techniques is sufficient for the act of teaching. Regarding the pedagogical training for teaching in higher education, we note that the professionalization of professors is shrouded in many forces, sometimes favorable, sometimes antagonistic, which further complicates the situation of teaching in university settings, since the lack of teacher training hinders the establishment of a professional identity. Finally, in discussing the role of pedagogical counseling, we testify that the performance of the ASPED is a very controversial topic, incorporating from punctual, urgent issues aimed at meeting the market needs of a private institution, through the pedagogical training of professors, to monitoring professors in curriculum reform processes of undergraduate courses, reviewing assessment practices in education and the registration and promotion of innovative teaching practices.